Analysis of Livelihood of Rural Irrigated Crop Farmers in Kano State, Nigeria - Tafida, Ahmadu; Michael, Amurtiya; Nandagoyang, Markson (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2022)
This study provided an analysis of the livelihoods of rural irrigated crop farmers in Kano State, Nigeria. The study’s specific objectives were to; describe the socio-demographic characteristics of the respondents, assess their livelihood assets, household wellbeing, and constraints. The study adopted a multistage sampling technique to collect primary data from 251 respondents drawn from 18 communities in six Local Government Areas of the State. In the analysis of the data, descriptive statistics and the Foster-Greer-Thorbecke poverty measurement were used. The study revealed that irrigated crop farming in the area is male-dominated (78.1%), and the practitioners were mostly small-scale farmers (average farm size of 1.8 ha). In terms of assets, this study revealed that most of the respondents were limited in natural, human, and financial capital. Poverty incidence was about 51%, with the lack of access to formal loans, decline in soil productivity, poor access to market, and lack of access to farm mechanization being prominent challenges of the people. Therefore, there is a need for the government and other key actors in the agriculture and financial sectors to ease farmers’ access to credit facilities and agricultural extension services.